Transmembrane Protein 39A Promotes the Replication of Encephalomyocarditis Virus via Autophagy Pathway - Li, Xiangrong; Ma, Ruixian; Li, Qian; Li, Shengjun; Zhang, Haixia; Xie, Jingying; Bai, Jialin; Idris, Adi; Feng, Ruofei (Frontiers in Microbiology, 2019)
Encephalomyocarditis virus (EMCV) causes encephalitis, myocarditis, neuropathy, reproductive disorders and diabetes in animals. EMCV is known to induce cell autophagy; however, the molecular mechanisms underlying this remains unclear. Here, we show that the type Ⅲ-transmembrane protein, transmembrane protein 39A (TMEM39A), plays a critical role in EMCV replication. We showed that EMCV GS01 strain infection upregulated TMEM39A expression. Importantly, EMCV induced autophagy in a range of host cells. The autophagy chemical inhibitor, 3-MA, inhibited EMCV replication and reduced TMEM39A expression. This is the first study demonstrating TMEM39A promoting the replication of EMCV via autophagy. Overall, we show that TMEM39A plays a positive regulatory role in EMCV proliferation and that TMEM39A expression is dependent on the autophagy pathway.